(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Awareness of the special role of water and its exceptional social importance in terms of the human right to safe and sufficiently clean water became the basis for solving the problem of ensuring water security. Water is recognized as an extremely limited and valuable natural resource that is property for present and future generations.